Penerapan Mirror Therapy Terhadap Kekuatan Otot Pasien Stroke Non Hemoragik Di RSUD Dr. Moewardi Surakarta - Annisa Ukti Laksmana Putri; Ida Nur Imammah; Isti Haniyatun (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Background: Stroke is one of the causes of disability in adults today, stroke has an impact on the function of the extremities of the body, especially the upper extremities. The impact of lowering the upper extremities is the disruption of daily activities such as bathing, eating, dressing, working and other types of activities that use the upper extremities. To increase the upper extremity muscles, therapy is carried out using mirrors, especially on the upper extremities. Objective: To determine the effect of Mirror therapy on muscle strength in non-hemorrhagic stroke patients. Method: Implementation was carried out using the case study method to 2 respondents, for 3 consecutive days a day for 15 minutes in the afternoon. Findings: Based on the results of the application that has been carried out, there is a decrease in muscle strength in non-hemorrhagic stroke patients Implication: Mirror therapy is expected to be applied in nursing practice by doing it 2x a day thereby giving maximum results.